2002
DOI: 10.1128/cdli.9.1.28-32.2002
|View full text |Cite
|
Sign up to set email alerts
|

Increased Anionic Peptide Distribution and Intensity during Progression and Resolution of Bacterial Pneumonia

Abstract: Anionic peptides (APs) are small anionic antimicrobial peptides composed of 7 aspartic acid residues and are produced in the lungs of humans, sheep, and cattle. Although expression by epithelial cells of some antimicrobial peptides (e.g., ␤-defensins) of humans and ruminants is increased in response to acute infection, AP expression is not increased during acute infection, which suggests that the expression of the latter peptide is constitutive. In this study, the degree of AP expression during the progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…During acute M. haemolytica infection of calves, anionic peptide expression was not increased suggesting constitutive expression (Fales-Williams et al, 2002a). A similar study in sheep suggested anionic peptide was increased only during chronic M. haemolytica pneumonia the source of the anionic peptide was reparative hyperplastic epithelium (Fales-Williams et al, 2002b). Efforts to assess activity against M. haemolytica bacteria showed within minutes of inoculation anionic peptide bound to the bacteria causing degenerative ultrastructural changes suggesting bacteriocidal effects (Heidari et al, 2002).…”
Section: Anionic Peptidementioning
confidence: 94%
See 1 more Smart Citation
“…During acute M. haemolytica infection of calves, anionic peptide expression was not increased suggesting constitutive expression (Fales-Williams et al, 2002a). A similar study in sheep suggested anionic peptide was increased only during chronic M. haemolytica pneumonia the source of the anionic peptide was reparative hyperplastic epithelium (Fales-Williams et al, 2002b). Efforts to assess activity against M. haemolytica bacteria showed within minutes of inoculation anionic peptide bound to the bacteria causing degenerative ultrastructural changes suggesting bacteriocidal effects (Heidari et al, 2002).…”
Section: Anionic Peptidementioning
confidence: 94%
“…These peptides are expressed constitutively and mediate antimicrobial activity against Gram-negative and Gram-positive bacteria (Fales-Williams et al, 2002b;Brogden et al, 1996Brogden et al, , 1997.…”
Section: Anionic Peptidementioning
confidence: 99%
“…The PEO-peptide conjugate is sufficiently short to facilitate diffusion [42] through solvated PEO during electrospinning, whereas the PEO segment of the conjugate is still long enough to i) permit co-crystallization with the PEO matrix to anchor the oligopeptide along the fiber surface, and ii) possibly function as a spacer between the fiber surface and the biofunctional peptide segment. While the anionic oligopeptide sequence in (SEE) 3 -PEO may exhibit antimicrobial activity [43] (which is beyond the scope of this work), it is expected to alter solution properties before, as well as respond to the applied electric field during, electrospinning. Solution viscosities measured at different (SEE) 3 -PEO concentrations (relative to PEO) in aqueous PEO solutions reveal two trends: i) an increase in PEO concentration promotes an increase in viscosity, and ii) an increase in (SEE) 3 -PEO content at fixed PEO Figure 1.…”
mentioning
confidence: 99%
“…71,150 Anionic peptides are small, hydrophilic peptides that contain homopolymeric regions (e.g., 5-7 residues) of aspartic acid, which are responsible for their negative charge. 16,41 They have been detected in the lungs, bronchoalveolar lavage (BAL) fluid, and pulmonary surfactant of humans, sheep, and cattle. For maximal bactericidal activity, APs require zinc as a cofactor, which may allow the peptide to overcome the net negative charge once on the microbial surface.…”
Section: Antimicrobial Factors Of Airway Surface Liquidmentioning
confidence: 99%